COVID-19 vaccination in patients with multiple myeloma: a consensus of the European Myeloma Network. Issue 12 (December 2021) - Ludwig, Heinz; Sonneveld, Pieter; Facon, Thierry; San-Miguel, Jesus; Avet-Loiseau, Hervé; Mohty, Mohamad; Mateos, Maria-Victoria; Moreau, Philippe; Cavo, Michele; Pawlyn, Charlotte; Zweegman, Sonja; Engelhardt, Monika; et al.
Summary: Patients with multiple myeloma frequently present with substantial immune impairment and an increased risk for infections and infection-related mortality. The risk for infection with SARS-CoV-2 virus and resulting mortality is also increased, emphasising the importance of protecting patients by vaccination. Available data in patients with multiple myeloma suggest a suboptimal anti-SARS-CoV-2 immune response, meaning a proportion of patients are unprotected. Factors associated with poor response are uncontrolled disease, immunosuppression, concomitant therapy, more lines of therapy, and CD38 antibody-directed and B-cell maturation antigen-directed therapy. These facts suggest that monitoring the immune response to vaccination in patients with multiple myeloma might provide guidance for clinical management, such as administration of additional doses of the same or another vaccine, or even temporary treatment discontinuation, if possible. In those who do not exhibit a good response, prophylactic treatment with neutralising monoclonal antibody cocktails might be considered. In patients deficient of a SARS-CoV-2 immune response, adherence to measures for infection risk reduction is particularly recommended. This consensus was generated by members of the European Multiple Myeloma Network and some external experts. The panel members convened in virtual meetings and conducted an extensive literature research and evaluated recently published data and work presented at meetings, as well as findings from their own studies. The outcome of the discussions on establishing consensus recommendations for COVID-19 vaccination in patients with multiple myeloma was condensed into this Review.